Hubungan Kebijakan Manajemen, Ketersediaan Fasilitas di Tempat Kerja, dan Penerapan 3M (Memakai Masker, Mencuci Tangan dan Menjaga Jarak) Pekerja dengan Pencegahan dan Pengendalian Covid-19 : The Relationship Between Management Policies, Workplace Facilities Availability, and Employee Adherence to (Wearing Masks, Washing Hands, and Maintaining Distance) with COVID-19 Prevention and Control - Manurung, Eka Noviyanti (Journal of Nursing Education and Practice, 2022)
Introduction: Corona Virus Disease (Covid-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) which is transmitted from symptomatic people to other people in the vicinity through droplets (such as coughing or sneezing), objects or surfaces that are touched. contaminated with droplets of an infected person and on the mucosa (mouth and nose). Objective: To find out the relationship between management policies, availability of facilities in the workplace, and the implementation of 3M workers with the prevention and control of Covid-19 at PT. Saranabaja Gate 2021. Methods: This study uses a quantitative method with a cross-sectional approach. The population in this study was 386 people. The sampling technique used in this study was a simple random sampling of as many as 79 people. The research instrument used a questionnaire and was tested statistically with the Chi-Square Test. Results: The results of the Chi-Square test show the value of the relationship between management policies (p=0.000), availability of facilities in the workplace (p=0.000), and the application of 3M workers (p=0.000) with Covid-19 prevention and control (p=0.000). Conclusion: There is a significant relationship between Management Policy, Availability of Facilities at Work, and Implementation of 3M (wearing masks, washing hands and keeping distance) Workers with Covid-19 Prevention and Control at PT. Saranabaja Gate 2021.